DISCOVERING THE GLOBAL LANDSCAPE OF HEALTH EMERGENCY DISASTER RISK MANAGEMENT IN DISASTER PLANNING: A BIBLIOMETRIC REVIEW - `Ainatul Fathiyah Abdul Rahim; Irina Safitri Zen; Alias Abdullah (Journal of Islamic, Social, Economics and Development, 2023)
This study aims to provide a bibliometric analysis of health disaster risk management using one of the indexed journal databases: Scopus. This study analysed the development trend and literature published in health disaster risk management in the context of disaster planning. The related articles' citation, bibliographical, and author keyword information were exported to VOSviewer. The VOSviewer was used for the analysis, which involved 1137 documents related to health emergency disaster risk management studies. The findings showed that there are increasing trends of publications related to health disaster risk management globally, especially after 2002. Most health emergency disaster risk management documents published in the Scopus database between 1976 and 2022 were original research articles, mainly written in English. The present study's findings are hoped to provide valuable insights and information for the researchers to determine future directions related to health emergency disaster risk management studies in the context of disaster planning.